WOOD AS A PRIMARY SELECTION OF MATERIAL FOR FURNITURE PRODUCTION - Namicev, Petar; Petrovski, Mihail (Journal of process management and new technologies, 2019)
This paper analyzes the influence of wood as the primary choice of material for furniture production. The wood, with its physical, chemical and mechanical properties, stands out from other materials when making a selection of material for furniture production. The wood possesses excellent physical properties, hardness, strength and density, chemical properties, wood does not rust and mechanical properties, elasticity, bending strength and tensile strength. Each type of wood has its own specific propertiesthat make it unique, even the same kind of wood grown in a different place has different properties, the oak has great strength and is therefore difficult to work while the beech has less firmness then the oak and therefore it is easier for machining. Proper choice of material also exerts a great influence on the very design of the piece of furniture. The choice of material depends on which design will be used in the manufacture of furniture. A well thought-out design can be adapted to the choice of material sometimes, but with wood as the primary choice of material for furniture production the design itself gets on quality.